STUDY OF THE LEVEL OF UTILIZATION AND POSSIBLE DEVELOPMENT OF FISHERIES PORT OF CAROCOK TARUSAN BEACH, PESISIR SELATAN DISTRICT, WEST SUMATERA - Viki Okta Yuanda; Alit Hindri Yani; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTFishing Port of Carocok Tarusan Beach is located in Koto XI Sub-District Tarusan Selatan Pesisir Regency, West Sumatra Province, PPP Carocok is equipped with basic, functional and supporting facilities. The facilities that are owned must be utilized and there is a need for a strategy / analysis that provides input for development priorities for sustainable facilities so that PPP Carocok can serve maximum activities in the port. This study aims to determine the level of utilization of facilities and the possibility of developing PPP Carakan Tarusan. The method used in this study is themethod survey and uses data analysis, namely the analysis of utilization rates and Scale analysis Likert. Facilities analyzed for utilization rates are dock 42.28%, port pool area 45.29%, port pool depth 55%, 33% plaster and 64% land. From these results it can be concluded that the optimization of functional and overall supporting basic facilities has not been optimally utilized, from the analysis of the Likert Scale development priority is the range of scales of 15-20. Keywords:Utilization Rate, Development, Port Facilities